Enhanced energy storage property achieved in Na0.5Bi0.5TiO3-based ferroelectric ceramics via composition design and grain size tuning. Issue 15 (December 2022) - chen, Yong; Huang, Yue; Zuo, Yuandong; Wang, Husheng; Liu, Kun; Fan, Baoyan; Zhang, Qingfeng; Zhang, Guangzu; Jiang, Shenglin; Shen, Meng
Abstract: Dielectric energy storage capacitors have been explored to obtain excellent energy storage density along with high energy storage efficiency with the development of electronic devices. In this work, linear dielectric CaTi0.5 Zr0.5 O3 is introduced into Bi0.5 Na0.5 TiO3 -NaNbO3 matrix to form 0–3 type composites to vary the size and conductivity of the composite grain, which lead to ultra-high breakdown electric field of 410 kV/cm and the quasi-linear hysteresis loops. Meanwhile, linear dielectric does not change the characteristic of ferroelectric, and thus composites maintain high maximum polarization of 26.4 μC/cm 2 . Integrating the advantages of linear dielectric and ferroelectric, an excellent recoverable energy density of 4.93 J/cm 3 with an efficiency of 93.3% have been achieved in BNT-NN/7 wt%CZT ceramics. This work contributes to the development of dielectric energy storage capacitors for practical applications in pulsed power devices.